Preparation and Characterization of Novel Nanofibrous Composites Prepared by Electrospinning as Multifunctional Platforms for Guided Bone Regeneration Procedures - Aleksandra Sierakowska-Byczek; Julia Radwan-Pragłowska; Łukasz Janus; Tomasz Galek; Natalia Radwan-Pragłowska; Karol Łysiak; Piotr Radomski; Mirosław Tupaj (Applied Sciences)
Prosthetics, a rapidly advancing field in dentistry, aims to improve patient comfort and aesthetics by addressing the challenge of replacing missing teeth. A critical obstacle in dental implantation is the condition of the jawbone, which often necessitates reconstruction prior to implant placement. Guided bone regeneration (GBR) and guided tissue regeneration (GTR) techniques utilize membranes that act as scaffolds for bone and tissue growth while serving as barriers against rapidly proliferating cells and pathogens. Commonly used membranes, such as poly(tetrafluoroethylene) (PTFE) and collagen, have significant limitations—PTFE is non-bioresorbable and requires secondary removal, while collagen lacks adequate mechanical strength and exhibits unpredictable degradation rates. To overcome these challenges, nanofiber membranes produced via electrospinning using polylactic acid (PLA) were developed. The novel composites were functionalized with bioactive additives, including periclase (MgO) nanoparticles and polydopamine (PDA), to enhance osteoblast adhesion, antibacterial properties, and tissue regeneration. This study comprehensively evaluated the biological, mechanical, and physicochemical properties of the prepared nanofibrous scaffolds. Experimental results revealed controlled degradation rates and improved hydrophilicity due to surface modifications with PDA and MgO. Moreover, the nanofibers exhibited enhanced swelling behavior, which promoted nutrient exchange while maintaining structural integrity over prolonged periods. The incorporation of bioactive additives contributed to superior osteoblast proliferation, antibacterial activity, and growth factor immobilization, supporting bone tissue regeneration. These findings suggest that the developed nanofibrous composites are a promising candidate for GBR and GTR applications, offering a balanced combination of biological activity, mechanical performance, and degradation behavior tailored for clinical use.